Heterospecific sociality of birds on beaches from southeastern Brazil - Cestari, César [UNESP] (Sociedade Brasileira de Zoologia, 2009)
Studies on the sociality of heterospecific assemblages of birds have promoted a greater understanding of the types of interactions and survivorship between coexisting species. This study verified the group compositions in bird assemblages and analyzed the sociality of migratory and resident species on sandy beaches of southeastern Brazil. A transect was established on the median portion of beaches and all the groups of bird species (monospecific, heterospecific) and solitary individuals were registered four days per month from November 2006 to April 2007. The sociality of each species was calculated by its frequency in heterospecific groups, its proportional number of contacts with other species in heterospecific groups, and the number of species that it associated with. Semipalmated Sandpiper Calidris pusilla (Linnaeus, 1766) and Semipalmated Plover Charadrius semipalmatus Bonaparte, 1825 (both migratory) had the highest degree of sociality and did not show a preference to associate with either residents or migratory species. Sanderling Calidris alba (Pallas, 1764) (migratory) occupied the third position in the sociality rank and associated with migratory species frequently. Southern Caracara Carara plancus (Miller, 1777) and Black Vulture Coragyps atratus (Beschstein, 1793) (both resident) were uniquely found among heterospecific groups with necrophagous and resident species. Kelp Gull Larus dominicanus Lichtenstein, 1823 (resident) associated more frequently with resident species. The sociality in assemblages of birds may promote advantages such as an increased collective awareness in dangerous situations and indication of sites with abundant food sources.
Keywords: Association; competition; heterospecific groups; Nearctic migrants; shorebirds